Pengaruh Fitur Affiliate dan Live Streaming pada E-Commerce terhadap Minat Beli Konsumen di Jawa Barat - Saputra, Frastya Dwi; Siregar, Salim (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study examines the influence of affiliate and live streaming features on e-commerce platforms on consumer buying interest in West Java. The background is the rapid development of e-commerce in Indonesia and the increasing use of digital marketing strategies. The research was conducted using a quantitative approach and respondent selection through purposive sampling technique and online questionnaire distribution to 100 respondents in West Java who have experience using affiliate features or watching live streaming products in the last six months. Data analysis was conducted with multiple linear regression using SPSS. The research findings indicate that the affiliate feature has a significant positive impact on consumer purchase intention, while the live streaming feature has no significant effect partially. However, simultaneously, both features contribute significantly to purchase intention with a coefficient of determination of 49.5%. This indicates that affiliate strategies are more effective in driving purchasing decisions than live streaming. This study is expected to support the advancement of digital marketing practices and become a reference for e-commerce business practitioners in the West Java region.
Keywords: E-Commerce; Affiliate Marketing; Live Streaming; Purchase Intention; West Java